Estudo da incidência, identificação e parâmetros prognósticos dos hemangiomas e hemangiossarcomas em animais de companhia - Berselli, Michele (2011)
Blood vascular tumors (hemagioma and hemangiosarcomas) are common neoplasms in dogs and cats, although their frequency of diagnosis is lower than others neoplasms and may reach the skin or organ systems. The hemangioma is a benign, although it can cause organ dysfunction when reaching systemic organs. The hemangiosarcoma represents a serious problem, because their malignant nature is considered one of the soft tissue sarcomas of worse prognosis causing sudden death. In this sense, the objective was to identify the incidence, prognostic parameters and time and survival rate of pets suffering from hemangiomas and hemangiosarcomas. We conducted a survey of cases of hemangiomas and hemangiosarcomas in dogs and cats diagnosed at the Regional Diagnostic Laboratory, Federal University of Pelotas, during the period 1998 to 2010. We retrieved 53 samples from biopsies and/or necropsies. Of the total cases studied, 20 animals with neoplasms were monitored over a period of two years. In this study, we used histopathological parameters, invasion, survival time and location as criteria for assessing prognosis. Histological parameters were evaluated as histological arrangement, cell morphology, mitotic rate, peritumoral lymphoplasmocytic infiltrate, necrosis, hemorrhage, and invasion to adjacent tissues were compared with histological grade and survival of affected animals. The neoplasms affecting skin in 60% of samples. Hemangiosarcomas were much more common than hemangiomas. When histological parameters were compared, we observed that the location was statistically significant when compared to the morphology (p = 0.0001), as well as the amount of bleeding (p = 0.0001) and invasion (p = 0.029). Other parameters showed no relation with the histologic grade and/or survival, thus, are not considered predictive prognostic factors. In this study, the survival rate for dogs with cutaneous hemangiomas and hemangiosarcomas was 90.91% while patients with systemic tumors was 41.67% in two years. From the results, we conclude that the intensity and location of invasion are important prognostic factors predictive for hemangiosarcomas in dogs and cats. Other parameters showed no relation with the histologic grade and/or survival, thus, are not considered predictive prognostic factors. The time and survival rate were lower for cats and dogs suffering from visceral hemangiosarcomas and the prognosis is generally unfavorable.